The Role of Artificial Intelligence in Research Methodology - Kujur, Anjela Swarndipika (AG Volumes, 2025)
A tedious and intricate procedure, thematic analysis is a part of qualitative research. The potential for improving and partially automating theme analysis has been raised by the development of “generative artificial intelligence (A.I.)”, particularly big language models. Review the many studies on the use of artificial intelligence in research technique in this article. This review emphasizes the transformative role of Artificial Intelligence, particularly tools like Chat GPT, in enhancing research methodology. AI streamlines data analysis, fosters deeper insight generation, and supports personalized workflows, especially in qualitative research. However, its effectiveness hinges on user understanding, ethical awareness, and critical engagement. While AI can supplement human expertise, it should not replace it. A synergistic relationship between AI and human judgment is essential for valid outcomes. Future efforts must focus on developing standardized guidelines and fostering transparency to ensure responsible, meaningful, and contextually appropriate integration of AI in global research practices.